Reflections on post-Marxism Laclau and Mouffe's project of radical democracy in the 21st century - Sim, Stuart 1943- (Global discourse, 2022)
First published as a special issue of Global Discourse, this book explores the theoretical position of post-Marxism and investigates its significance in recent global political developments such as Brexit, Trump and the rise of the far right